Formal modeling and analysis of timed systems : 16th International Conference, FORMATS 2018, Beijing, China, September 4-6, 2018, Proceedings /: 16th International Conference, FORMATS 2018, Beijing, China, September 4-6, 2018, Proceedings. (2018) - Unknown
No abstract available